Wetenschap in een regionale context: Een reactie - Oosterhaven, Jan; Molema, Marijn; Melis, Korrie (Studium, 2013)
Science in a regional context: A reaction (and a response to this reaction)Melis and Molema, in an article in this journal in 2012, argue that the relation between university research and its region is two-sided. In a reaction, Oosterhaven, one of the stakeholders of the described case of the group of spatial economists at the University of Groningen (RUG), argues that the relationship in this case, in both directions, is much stronger than is indicated by Melis and Molema. Oosterhaven claims that difficult, actual regional policy questions led to at least two important scientific innovations in the treatment of supply-driven, forward linkages in respectively, regional input-output models and applied general equilibrium models. In the other direction, Oosterhaven argues that two major social cost-benefit analyses done by the spatial economists at the RUG most likely led to decisions to spend billions more on two successive regional policy programmes, than otherwise would have been spend. Furthermore, over time, the relation has become stronger and even circular. At the end, Melis and Molema respond to Oosterhaven’s arguments.